Validating a theoretical model of citizens' trust in tourism development. (February 2021) - Pagliara, Francesca; Aria, Massimo; Russo, Lucia; Della Corte, Valentina; Nunkoo, Robin
Abstract: This research establishes the theoretical link between the development of tourism and citizens' trust. The research is grounded in political economy of state intervention in tourism and draws from social exchange theory to build the theoretical model. The latter incorporates variables such as trust, power, knowledge, and benefits and costs of tourism, which are central to any exchange process between social actors. The model distinguishes and proposes a theoretical relationship between domain specific political trust and generic political trust. The former refers to citizens' trust in local government in the specific context of tourism development while the latter refers to citizens' general level of trust in local government. The model is tested using data collected from residents of the metropolitan area of Naples, Italy. Results suggest that residents' trust in local government in the specific context of tourism strongly influences their general level of trust, suggesting a spill-over effect of political trust. We demonstrated empirically that political trust in the context of tourism and the general trust in an institution are theoretically distinct concepts. The constructs we used to conceptualize tourism development has distinct influence on the two dimensions of political trust. Highlights: Theoretical link between tourism and citizens' trust. Spill-over effect of political trust. Distinct concepts of political trust for tourism and trust in institutions.